Porphyromonas gingivalis Periodontal Infection and Its Putative Links with Alzheimer’s Disease - Sim K. Singhrao; Alice Harding; Sophie Poole; Lakshmyya Kesavalu; StJohn Crean (Mediators of Inflammation)
Periodontal disease (PD) and Alzheimer’s disease (AD) are inflammatory conditions affecting the global adult population. In the pathogenesis of PD, subgingival complex bacterial biofilm induces inflammation that leads to connective tissue degradation and alveolar bone resorption around the teeth. In health, junctional epithelium seals the gingiva to the tooth enamel, thus preventing bacteria from entering the gingivae. Chronic PD involves major pathogens (Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia) which have an immune armoury that can circumvent host’s immune surveillance to create and maintain an inflammatory mediator rich and toxic environment to grow and survive. The neurodegenerative condition, AD, is characterised by poor memory and specific hallmark proteins; periodontal pathogens are increasingly being linked with this dementing condition. It is therefore becoming important to understand associations of periodontitis with relevance to late-onset AD. The aim of this review is to discuss the relevance of finding the keystone periodontal pathogen P. gingivalis in AD brains and its plausible contribution to the aetiological hypothesis of this dementing condition.